Such a Sight: Fire and Prairie Identity - Julie Courtwright (Symphony in the Flint Hills, 2014)
There were (and are) many ways to see a prairie fire—both literally and figuratively. Nineteenth-century tallgrass prairie dwellers, for instance, saw them in every conceivable manner–the flames crawling across the landscape during light winds and racing across it during gales.
Keywords: fire; prairie; grassland; grass; native; tallgrass; Flames; landscape; burning; burn; danger; land; beautiful; newcomers; reaction; lifestyle; historic